Higher education, graduate talent and the prospects for social mobility in China's innovation nation. (2021) - Brown, Phillip; Sadik, Sahara; Xu, Jing
Highlights: HE Reforms to create employable talent will not increase Social Mobility; Corporate 'War for Talent' is contributing to educational inequalities; Inequity and social mobility need wider reforms beyond education. Digital Innovation unlikely to lead to a major increase in 'knowledge' work Positional theory shows why more access to HE may not increase social inclusion. Abstract: This article examines China's response to issues of social inequity, talent management and social mobility through an analysis of HE policies aimed at transforming China into an innovation nation, alongside the views of corporate managers and executives. Our analysis identifies a positional convergence between China's elite universities and corporate hiring strategies, which renders the 'vocational turn' in HE as part of its digtial innovation strategy, unlikely to narrow educational and labor market inequalities in relative life-chances. What is identified in China is widely applicable, highlighting that social equity and social mobility cannot be delivered through neo-liberal models of technological change.